Nursing Management in Neonate Intensive Care Unit (NICU) Hospital X Bandung - Samual M Simanjuntak; Ayu Rahayu Maria Magdalena Sijabat; Cindy Grace Harefa; Samot Lydia Tambunan (Eduvest - Journal of Universal Studies, 2025)
Nursing management in the Neonate Intensive Care Unit (NICU) of Hospital X Bandung is an important aspect in providing optimal health services for infants who require intensive care. This study aims to evaluate the implementation of nursing management in the NICU, focusing on aspects of planning, organizing, directing, staffing, and supervising. The method used was descriptive qualitative analysis through observation and interviews with the nursing team and hospital management. The results showed that although nursing management functions were well implemented, there were challenges such as a lack of clarity in the organizational structure and the need to improve nurse certification. Unit performance indicators showed positive achievements, especially in handling autoextubation cases. However, the implementation of Standard Operating Procedures (SOPs) in the NICU unit still needed to be improved, as some procedures were not well documented. The conclusion of this study emphasizes the need for improvements in nursing management to improve service quality and the importance of continuous training for nurses. Recommendations include strengthening coordination between medical teams and improving SOPs in the NICU, in order to increase the effectiveness of health services for neonate patients. This study is expected to make a positive contribution to hospital managers and nursing practitioners in improving the quality of services in the NICU.